Examining the Nonlinear Asymmetric Effects of Tax Revenues on Financial Development in Iran: Hatemi-J Asymmetric Causality and NARDL Analysis - Ali Al-Tameemi, Ahmed Obaid; Sojoodi, Sakineh; Barghi Oskooee, Mohammad Mahdi (Business, Marketing, and Finance Open, 2027)
The financial system plays a pivotal role in investment and saving decisions, thereby exerting a significant influence on economic growth. Consequently, identifying the determinants of financial development has attracted considerable attention from researchers and policymakers. At the same time, tax revenue, as a primary source of government income, is of critical importance due to its effects on public investment, social services, debt financing, and budget deficit management. Given the crucial role of government tax revenue in shaping both public and private investment decisions, the present study investigates the asymmetric causality between tax revenue and financial development in Iran over the period 1970–2024. To this end, the Hatemi-J asymmetric causality test and the Nonlinear Autoregressive Distributed Lag (NARDL) model are employed. The results reveal a unidirectional asymmetric causal relationship running from tax revenue to financial development. Specifically, positive shocks in tax revenue exert a negative impact on financial development, while negative shocks exert a positive impact, confirming the presence of asymmetry. Moreover, economic growth and government expenditure have positive and statistically significant effects on financial development, whereas inflation exerts a negative and significant impact. The error correction term coefficient is estimated at −0.50, indicating that approximately 50 percent of short-run deviations from the long-run equilibrium are corrected within each period.